The Parent-Child Relationship and it’s Legal Contexts - Dyrdół, Małgorzata (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
The subject of the dissertations in the article is law regulations relating to parents and their children, referring to parental authority on one hand and children’s rights on the other. The starting point for these dissertations is study of the parent–child relationship, including its types and ways of expression, cultural diversity and transformations through which this relationship has undergone.
Keywords: interpersonal relations; way of upbringing; parental attitudes; freedom; compulsion; parental authority; children; children's rights; children's subjectivity